Supercapacitor electrodes from activation of binderless green monoliths of biomass self-adhesive carbon grains composed of varying amount of graphene additive - Jasni M.R.M.; Deraman M.; Suleman M.; Zainuddin Z.; Othman M.A.R.; Chia C.H.; Hashim M.A. (Institute for Ionics, 2024)
Indexed by WOS/SCOPUS/ERA